COMPARISON OF FOOD WASTE MANAGEMENT POLICES BETWEEN GREECE AND ARMENIA: POSSIBLE RECOMMENDATIONS FOR ARMENIA - Sargis GEVORGYAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The topic of food waste management has become a global discussion in recent years, but it is still not widely addressed in Greek and Armenian societies. This can be attributed to the common cultural and historical backgrounds of these countries. This study explores waste management practices in both countries, with a specific focus on their respective national frameworks and initiatives. The study critically discusses Greece's National Waste Prevention Programme (NWPP) and extrapolates key policies and strategies pertinent to the Armenian context. Moreover, the current geopolitical changes and their potential influence on the food waste management system of Armenia have been discussed. Cultural and historical backgrounds necessitate a comparative examination between these two nations' policies. Employing a comprehensive document analysis using a deductive, concept-driven approach facilitated by docAnalyzer.ai, this study identifies substantial deficiencies within existing policy documents. It underscores the need for enhanced education, increased investments, and strengthened collaborative efforts as significant factors crucial for effecting systemic transformation. Addressing these gaps through informed policy interventions can enable both governments to implement successful models of food waste management and foster circular economies adjusted with respective socio-economic landscapes.